KEBUTUHAN PERAWATAN ORTODONSI SISWA SEKOLAH DASAR SUMBERSARI V KECAMATAN SUMBERSARI KABUPATEN JEMBER DENGAN MENGGUNAKAN INDEKS HANDY CAPPING MALOCCLUSION ASSESSMENT RECORD (HMAR) - Fajrin, Lailatul; Sutjiati, Rina (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Malocclusion is that deviate from normal occlusion. As a result of malocclusion cause abnormal function, communicative disorders such as speech, and aesthetic. Assessment or measurement of the severity of malocclusion index malocclusion using. A number of indices are applied include HMAR index (HANDYCAPPING MALOCCLUSION ASSESSMENT RECORD). The purpose of this study was to determine the severity of malocclusion in grade VI Elementary School District Sumbersari V Sumbersari, City Administration Jember using HMAR index. The subjects of this study were 36 students consisting of 21 women and 15 male students of class VI students Sumbersari Elementary School, City Administration Jember aged between 12-13 years. Analysis of the data used in this research is descriptive analysis. The results of this study can be concluded that the severity of malocclusion and need for orthodontic treatment in students Sumbersari V Elementary School District Administrative City Sumbersari Jember is high.